DELLA MUTATIONS IN PLANTS WITH SPECIAL EMPHASIS ON WHEAT - G. A. Chebotar; S. V. Chebotar; Yu. M. Sivolap (Вавиловский журнал генетики и селекции)
DELLA proteins are a subfamily of transcriptional regulators from the GRAS protein family. They act as growth repressors. Gibberellins (GA) promote growth by overcoming the DELLA-mediated growth restraint. A number of dominant mutations in highly conserved orthologous DELLA genes are known in various plant species. These mutations reduce plant height owing to production of more active forms of growth repressors. The aim of the current study is to estimate the genetic similarity of DELLA nucleotide and amino acid sequences stored in GenBank and to identify mutant and wild type alleles that encode DELLAs in modern Ukrainian winter bread wheat varieties. We have performed nucleotide and amino acid sequence search and alignment of the Rht-D1 wheat dwarfing gene and DELLA-encoding genes of other plant species with BLAST and MUSCLE software. A dendrogram illustrating phylogenetic relations among DELLA sequences of 35 plant species has been constructed using MEGA v5. In addition, PCR-based genotyping for the major wheat dwarfing genes Rht-B1 and Rht-D1 has been performed in wheat cultivars from different regions of Ukraine. It is shown that the mutant Rht-D1b allele is the commonest dwarfing allele among those tested in Ukrainian wheat cultivars (68 %), but its distribution over Ukraine is not random.